Tensões e prazeres: um estudo sobre a paternidade contemporânea, novos desafios - Benedito, Larissa Caroline (2025)
This work addresses the unique experience of parenthood, highlighting the initial developmental period of a family, when parents and babies are in the process of formation. Drawing on several psychoanalytic authors, the author argues that parenthood is not instinctive, as parents are "born" alongside their babies; it is a unique experience, especially regarding the psychological development involved in pregnancy. She also points to a transformation in contemporary family dynamics, with fathers becoming more involved and dedicated to caring for their babies, from pregnancy to postpartum. Concepts from Winnicott are revisited, highlighting the changing role of the father. Once seen as the protector of the mother-baby relationship, today he is an integral part of this "duo." Parenthood has become a shared commitment between both. This discussion uses several guiding questions: What are the challenges of contemporary life when it comes to becoming a father? Is a father capable of doing everything a mother does for her baby, especially early in life? Finally, it reflects on how initiatives like the "Pregnant Women's Club," discussion groups, and NGO projects on parenting are instrumental in driving this movement for chang